Effects of hydraulic head and basin geometry physical parameters on the vortex turbine hydraulic efficiency - Tan, Jian Hong (2018)
Gravitational Water Vortex Power Plant is a green technology where energy is extracted from water vortex instead of hydraulic head. This type of power plant is advantageous because of its capability to exploit the low-head sites. However, lack of experimental and theoretical literatures limit the development of this technology. This thesis describes the effects of the penstock's geometry and outlet diameter on the efficiency of the power plant. A prototyped power plant that simulates the lowhead river and power plant was fabricated. The parameter of this thesis includes six penstock models (A, B, C, D, E and F) to represent the different geometries of penstock, five outlet diameters (0.052 m, 0.056 m, 0.064 m, 0.072 m, 0.076 m) and five inlet flow rates (5.6 m3/h, 6.4 m3/h, 7.2 m3/h, 8.0 m3/h and 8.8 m3/h). These parameters were tested accordingly and the turbine rotational speed, vortex height and resistance force were recorded. The power input, power output and efficiency were then calculated using appropriate formula and analysis were carried out to study their effects on the performance of the prototype. It was found that the efficiency of the prototyped power plant reduced due to the larger penstock's feeding width of penstock model B and C compared to other four models. Peak efficiencies recorded on penstock model B and C were between 17 % to 24 % and 13 % to 21 % respectively at 8.8 m3/h. At similar flow rate, the other four penstocks' efficiency yields 20 % to 30 %. The prototype was found to perform best (efficiency of 28.29 %) when penstock model D was installed along with outlet diameter of 0.072 m at inlet flow rate of 8.8 m3/h. The performance of the prototype was also found to increase with increasing inlet flow rate up to 8.8 m3 /h. Other than that, penstock models A, D, E, and F was found to have insignificant effects on the performance of the prototype. Performance of the prototype was found to be better when the ratio of outlet diameter to basin diameter was kept between 0.14 to 0.18.